Rapid three-dimensional imaging of individual insulin release events by Nipkow disc confocal microscopy. (25th October 2006) - Rutter, G.A.; Loder, M.K.; Ravier, M.A.
Abstract : Minute-to-minute control of the release of insulin by pancreatic β-cells in response to glucose or other stimuli requires the precise delivery of large dense-core vesicles to the plasma membrane and regulated exocytosis. At present, the precise spatial organization at the cell surface and the nature of these events ('transient' versus 'full fusion') are debated. In order to monitor secretory events simultaneously over most of the surface of clusters of single MIN6 β-cells, we have expressed recombinant neuropeptide Y-Venus (an enhanced and vesicle-targeted form of yellow fluorescent protein) as an insulin surrogate. Individual exocytotic events were monitored using Nipkow spinning disc confocal microscopy, with acquisition of a three-dimensional complete image (eight to twelve confocal slices) in <1 s, in response to cell depolarization. Corroborating earlier studies using TIRF (total internal reflection fluorescence) microscopy, this approach indicates that events occur with roughly equal probability over the entire cell surface, with only minimal clustering in individual areas, and provides no evidence for multiple events at the same site. Nipkow disc confocal imaging may thus provide a useful tool to determine whether event types occur at different sites at the cell surface and to explore the role of endocytic proteins including dynamin-1 and -2 in terminating individual exocytotic events.